Komunikasi Interpersonal Pustakawan Bagian Layanan Sirkulasi Perpustakaan Umum Kota Depok - Galih, Hadyan Aldio; Fauziah, Kiki (UI Scholars Hub, 2019)
This study discusses the interpersonal communication between librarians in the circulation service unit of Depok Public Library. The purpose of this research is to identify the quality of interpersonal communication between librarians in the circulation services unit. This research used qualitative approach with case study method. The results of this study indicate that the interpersonal communication between librarians in Depok Public Library when serving the library users was done properly and in a good manner, in general. However, research findings also indicate that the librarians tended to show a rather superior attitude toward the users. Such attitude made the librarians look less proactive and sympathetic when serving the users.